The Conflict Of Tradition And Modernity In Kavery Nambisan’s Mango-Coloured Fish - Suba; Dr. K. Ashok Kumar (Revista Electronica de Veterinaria, 2024)
In Kavery Nambisan’s  Mango- Coloured Fish, modernity serves as a pivotal theme that drives the narrative and character development. The protagonist, Shari, navigates the complexities of contemporary life as she confronts traditional societal expectations, particularly regarding marriage and personal autonomy. The novel captures Shari’s journey of self-discovery and her quest for independence, reflecting the broader cultural shifts occurring in India as younger generations seek to reconcile their identities with modern values. Through her rejection of an arranged marriage, Shari embodies the struggles faced by many young women who aspire to define their own futures while grappling with the pressures of family and tradition. Nambisan uses Shari’s experiences to highlight the transformative power of modernity in shaping individual lives and identities, ultimately portraying a nuanced perspective on the interplay between tradition and modernity in Indian society.